Exploration of sex differences in Rhes effects in dopamine mediated behaviors - Quintero GC (Dove Medical Press, 2011)
Gabriel C Quintero1,2, Daniela Spano31INDICASAT AIP, Centro de Neurociencias, Panamá, 2Department of Psychology, University of New Orleans, N Orleans, Louisiana, USA; 3CEINGE Biotechnologie Avanzate, Naples, ItalyAbstract: Studies have shown that Ras homolog enriched in striatum (Rhes) proteins are highly expressed in areas of the central nervous system that have high dopaminergic innervation. In this study, we used Rhes mutant mice (Wild type, Rhes KO, Rhes Heterozygous) of both sexes to explore differences in the effects of Rhes protein levels in basal levels of activity, anxiety, and stereotypy, in relation to sex. Adult male and female mice were evaluated in an open field test for measuring basal levels of activity and anxiety for 5 consecutive days, and they were tested in the apomorphine-induced stereotypy paradigm. Rhes protein levels affected basal levels of activity but it was not found to be related to sex differences. Moreover, a decrease in Rhes protein levels was linked to a nonsignificant anxiolytic effect, mainly in female mice. Finally, a decrease in Rhes protein levels does not affect dopamine D1 and D2 receptor (D1/D2) synergism in female or male mice. Together, these results suggest that Rhes protein levels affect locomotion activity, and have an influence in anxiety depending on sex; Rhes protein levels do not affect D1/D2 synergism in both sexes.Keywords: behavior, dopamine receptor, Rhes protein, mutant mice, sexes